(untitled) (Economic Journal of Nepal, 2011)
The article is an extract of the major findings of the author’s Ph. D. thesis submitted to The Faculty of Humanities and Social Sciences, Tribhuvan University. It is believed that the recommendations would help in maintaining and improving the financial performance of microfinance institutions such as Small Farmers Cooperative Limited (SFCL) and similar types of other microfinance institutions. The correlation of social mobilisation components andfitumcial performance of SFCLs has been presented based on the number of significance of dependent variables and degree of correlation ranking of independent variables categorized as first, second, third and fourth most important variables. The perception of SFCL officials from the sample SFCLs and concerned stakeholders were also studied and recommended appropriate strategy for improving their financial performance. Key words: Small farmers; Cooperative Limited; Economic development Economic Journal of Nepal A Quarterly Publication of the Central Department of Economics, Tribhuvan University, Kirtipur, Kathmandu Vol. 30, No.4, October-December, Issue No. 120, 2007 Page: 246-259 Uploaded date: 22 July, 2011